2019
DOI: 10.3390/ma12244107
|View full text |Cite
|
Sign up to set email alerts
|

Polylactide-Based Stent Coatings: Biodegradable Polymeric Coatings Capable of Maintaining Sustained Release of the Thrombolytic Enzyme Prourokinase

Abstract: The novelty of the study is the development, creation, and investigation of biodegradable polymeric membranes based on polylactide, that are capable of directed release of large molecular weight biomolecules, particularly, prourokinase protein (MW = 46 kDa). Prourokinase is a medication with significant thrombolytic activity. The created membranes possess the required mechanical properties (relative extension value from 2% to 10%, tensile strength from 40 to 85 MPa). The membranes are biodegradable, but in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…2, 3, and 4. It should be noted that the polylactide films we synthesized have much higher yield strength as compared to other polylactide polymers [28,29]. It shown that with increasing streptokinase concentration in the polymer, the ultimate tensile strength decreases.…”
Section: Discussionmentioning
confidence: 85%
“…2, 3, and 4. It should be noted that the polylactide films we synthesized have much higher yield strength as compared to other polylactide polymers [28,29]. It shown that with increasing streptokinase concentration in the polymer, the ultimate tensile strength decreases.…”
Section: Discussionmentioning
confidence: 85%
“…Every bare metal implant possesses limited bioactivity. In order to further initiate interaction with the biological tissue and enable better bonding between the bone and the implant, medications and therapeutic agents can be incorporated directly into the implant surface or applied via (biodegradable) polymeric matrixes [ 87 , 88 ]. If properly selected, such polymers can enhance the biocompatibility of the metal implant, mitigate corrosion, and enable the controlled and tunable release of active ingredients [ 18 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ].…”
Section: Coating Materials Selectionmentioning
confidence: 99%
“…Nano-and micromaterials contained of poly (lactic-co-glycolic acid) (PLGA) are promising candidates for many biomedical applications, in particular, oncology therapy, targeted drug delivery, and vaccine efficacy improvement [25][26][27]. PLGA is often used to make biodegradable stent coatings, as well as parts of the stents themselves and other materials used for implantation [28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%